2015
DOI: 10.1007/s00299-015-1859-9
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling revealed the regulatory mechanism of Arabidopsis seedlings response to oxidative stress from cryopreservation

Abstract: Elevated antioxidant status and positive abiotic stress response in dehydration enhance cell resistance to cryoinjury, and controlling oxidative damage via reactive oxygen species homeostasis maintenance leads to high survival. Cryoprotectants are important for cell survival in cryopreservation, but high concentrations can also cause oxidative stress. Adding vitamin C to the cryoprotectant doubled the survival ratio in Arabidopsis thaliana 60-h seedlings (seedlings after 60-h germination) cryopreservation. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(23 citation statements)
references
References 65 publications
0
22
0
1
Order By: Relevance
“…A more recent area of study is that of transcriptome changes that occur due to the stresses imposed throughout cryopreservation. Studies by Ren et al (2015) and Gross et al (2017) explored the regulation of transcripts in response to exposure to CPAs and LN on A. thaliana. Ren et al (2015) primarily looked at the effect of addition of vitamin C to PVS2, and its effect on genes related to ROS stresses.…”
Section: Transcriptome Profilingmentioning
confidence: 99%
See 1 more Smart Citation
“…A more recent area of study is that of transcriptome changes that occur due to the stresses imposed throughout cryopreservation. Studies by Ren et al (2015) and Gross et al (2017) explored the regulation of transcripts in response to exposure to CPAs and LN on A. thaliana. Ren et al (2015) primarily looked at the effect of addition of vitamin C to PVS2, and its effect on genes related to ROS stresses.…”
Section: Transcriptome Profilingmentioning
confidence: 99%
“…Studies by Ren et al (2015) and Gross et al (2017) explored the regulation of transcripts in response to exposure to CPAs and LN on A. thaliana. Ren et al (2015) primarily looked at the effect of addition of vitamin C to PVS2, and its effect on genes related to ROS stresses. It was seen that, compared with controls, plant tissue incubated in PVS2 with vitamin C upregulated genes associated with antioxidant formation as well as genes associated with ROS-scavenging.…”
Section: Transcriptome Profilingmentioning
confidence: 99%
“…ROS-induced oxidative stress is the fundamental trigger of cell death during cryopreservation [8]. Ren et al [7,9] utilized comparative transcriptomics to obtain genes response to cryoinjury and revealed that peroxidation was a key element affecting viability, and genes related to oxidative stress played important roles in Arabidopsis thaliana cryopreservation. Zhang et al [10] revealed that oxidative stress and apoptosis were the major factors which injure embryogenic callus during Agapanthus praecox cryopreservation.…”
Section: Introductionmentioning
confidence: 99%
“…AsA belongs to water-soluble antioxidants and is one of the most important vitamins widely distributed in various plants (Guerreiro et al 2010). Some previous studies have demonstrated that AsA plays important roles in the regulation of mitosis and cell expansion (Smirnoff and Wheeler 2000), in electron transport chain (T贸th et al 2009), and particularly, in scavenging of ROS (Ren et al 2015). AsA is an important antioxidant of the ROS scavenging mechanism; it helps to reduce peroxides (Potters et al 2010).…”
Section: Introductionmentioning
confidence: 99%